The distribution of selected Scarabaeoid (Coleoptera) taxa in South Africa and Namibia : prospects for their conservation - Chown, Steven Loudon (University of Pretoria, 2022)
Dissertation (MSc (Entomology))--University of Pretoria, 1999.